The application of metagenomic next-generation sequencing for Angiostrongylus eosinophilic meningitis in a pediatric patient: A case report - Liu, Jing; Tao, Jinhao; Chen, Weiming; Wang, Tingting; Chen, Xin; Shen, Meili; Ou, Qiuxiang; Zhang, Yunjian; Ding, Yifeng; Wu, Jufang; Cheng, Xunjia; Lu, Guoping; et al. (Frontiers in Public Health, 2022)
Background: Angiostrongylus eosinophilic meningitis (AEM) is a rare yet emerging disease caused by Angiostrongylus cantonensis infection. Its atypical symptoms may delay the diagnosis and cause fatal outcomes, especially in the early stages of infection and among children. Case presentation: Here we reported the use of metagenomic next-generation sequencing (mNGS) to facilitate the diagnosis and treatment of an 8-year-old boy with severe A. cantonensis infection. The mNGS tests consistently identified the infection of A. cantonensis prior to the detection by the immunologic method and confirmed it as AEM. Subsequently, we used mNGS to help monitor the treatment. Due to the severe condition, the addition of doxycycline with albendazole was determined by the multidisciplinary team (MDT) approach and showed positive effects. Conclusion: This case demonstrated the advantages of mNGS for early diagnosis of AEM in pediatric patients, highlighting its application for pan-pathogen detection. Our study also suggested the therapeutic option of adding doxycycline for the management of severe A. cantonensis infection in pediatric patients.